Impact of cataract surgery on quality of life in rural areas of Jharkhand: a community based cross-sectional study - Jagadeesh, Bharath; Gupta, Sagarika; Bhatnagar, Anuj (International Journal Of Community Medicine And Public Health, 2023)
Background: Cataract is the leading cause of blindness in India, accounting for approximately 66.2% of all blindness cases and accounting for 71.2% of all visual impairment cases. This study was conducted in 5 blocks of East Singhbhum and Saraikela-Kharsawan districts of Jharkhand to determine burden of cataract and the impact of cataract surgery on quality of life in the rural population. Methods: Community based cross sectional study was conducted between January 2023 to April 2023 among individuals residing in rural areas of Jharkhand using multi-stage sampling with a sample size of 692 individuals. Results: Prevalence of cataract amongst the study population was 23% (159) and there was a statistically significant improvement in the quality-of-life post cataract surgery. Conclusions: High prevalence of cataract increases the burden on existing health care system. Ongoing research and initiatives should focus on improving early detection and referral, providing comprehensive post-operative care to reduce the burden of cataract and improve the quality-of-life outcomes among the individuals.